If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -4 = x + x + x + x Combine like terms: 10 + -4 = 6 6 = x + x + x + x Combine like terms: x + x = 2x 6 = 2x + x + x Combine like terms: 2x + x = 3x 6 = 3x + x Combine like terms: 3x + x = 4x 6 = 4x Solving 6 = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 6 + -4x = 4x + -4x Combine like terms: 4x + -4x = 0 6 + -4x = 0 Add '-6' to each side of the equation. 6 + -6 + -4x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -4x = 0 + -6 -4x = 0 + -6 Combine like terms: 0 + -6 = -6 -4x = -6 Divide each side by '-4'. x = 1.5 Simplifying x = 1.5
| 4x^2-8x=11+x^2-8x+16 | | c(c+1)=0 | | x^2+2x-35=o | | (2x-8)=(100) | | 5x^2+7x+21=0 | | 129.25-6(18.5)=x | | 11(x-6)=7(x+7) | | (2x(4x+8x)2)2+(2x(4x-8x)2)2=512whatisx | | -6x^2+64x-270=0 | | 322/5.5=x | | 60(1)+x=8(1)+x | | 5-(1.19+.89)=x | | 60(1)+x=80(1)x | | 4xy*dx+((x^2)+1)*dy=0 | | 3a+2b=21 | | 4x-3(2x+5)(4-18x)=2x+4+12(3x-3)(3x-3) | | 3(p-9)=12(p-7) | | a-8=3 | | y^2+3y+2y+2=0 | | 2(x+8)=12(x-10) | | -12p+1=-xp+16 | | (-9-3i)(2+i)= | | -16+4x+1=5 | | 2x-y-z=-3 | | 7/x-3-1/2=3/x-4 | | 17=3x-19 | | 5(n-12)=12(n-9) | | Xp=12p+15 | | A=zv+q | | 12X^3/3X^2 | | 20y-5y=15-5y+5 | | 3/c=3/7 |